2018
DOI: 10.1128/jcm.01998-17
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Circulating Bordetella pertussis Strains in Europe during 1998 to 2015

Abstract: One reason for increased pertussis incidence is the adaptation of to vaccine-induced immunity by modulating its genomic structure. This study, EUpert IV, includes 265 isolates collected from nine European countries during 2012 to 2015 ( = 265) and compares the results to previous EUpert I to III studies (1998 to 2009). The analyses included genotyping, serotyping, pulsed-field gel electrophoresis (PFGE), and multilocus variable-number tandem-repeat analysis (MLVA). Genotyping results showed only small variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 29 publications
(47 reference statements)
4
35
2
2
Order By: Relevance
“…Typing of ACV antigen genes, ptxP , ptxA , prn , fim2 and fim3 among the 55 selected isolates from 2008 to 2016 revealed that ptxP3/ptxA1/fim2-1 isolates were predominant (51/55, 92.7%). Out of the 51 ptxP3 isolates, 50 isolates carried fim3-2 (also denoted as fim3B ) allele and only one had fim3- 1 (also denoted as fim3A ) [25,26]. Isolates with the allele profile ptxP3/ptxA1/prn2/fim3- 1 were predominant among ptxP3 isolates (42/51, 82.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typing of ACV antigen genes, ptxP , ptxA , prn , fim2 and fim3 among the 55 selected isolates from 2008 to 2016 revealed that ptxP3/ptxA1/fim2-1 isolates were predominant (51/55, 92.7%). Out of the 51 ptxP3 isolates, 50 isolates carried fim3-2 (also denoted as fim3B ) allele and only one had fim3- 1 (also denoted as fim3A ) [25,26]. Isolates with the allele profile ptxP3/ptxA1/prn2/fim3- 1 were predominant among ptxP3 isolates (42/51, 82.3%).…”
Section: Resultsmentioning
confidence: 99%
“…A prominent feature of B. pertussis evolution in ACV immunised host populations is the emergence and expansion of pertactin deficient strains [4]. Prn deficient strains were first reported in France, and now in many countries including UK, Canada, US and Australia [25,26,51–53]. Australia and US reported the highest percentages of Prn deficient isolates with 89.7% of the isolates from 2013 to 2017 in Australia and >85% in 2013 in the US [26,54].…”
Section: Discussionmentioning
confidence: 99%
“…During the WCV era, one PRN-deficient strain was found in Italy in the mid-1990s [4]. A recent study also shows a similar increase in many European countries using ACVs [2]. Interestingly, a decrease in frequency of PRN-deficient strains was reported in Japan, where the proportion of ACVs without PRN in use was increased in 2012 [5].…”
mentioning
confidence: 96%
“…PRN-deficient isolates were further studied by sequencing of the prn gene. Genotyping of prn, ptxP and ptxA genes of all isolates was performed as previously described [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation